2016
DOI: 10.1158/0008-5472.can-16-0346
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Responses to Neoadjuvant Chemotherapy in Breast Cancer: ACRIN 6691 Trial of Diffuse Optical Spectroscopic Imaging

Abstract: The prospective multi-center ACRIN 6691 trial was designed to evaluate whether changes from baseline to mid-therapy in a Diffuse Optical Spectroscopic Imaging (DOSI)-derived imaging endpoint, the Tissue Optical Index (TOI), predict pathologic complete response (pCR) in women undergoing breast cancer neoadjuvant chemotherapy (NAC). DOSI instruments were constructed at the University of California, Irvine and delivered to 6 institutions where 60 subjects with newly-diagnosed breast tumors (at least 2 cm in the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
129
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 56 publications
5
129
0
1
Order By: Relevance
“…36 A recent multi-center trial showed that diffuse optical spectroscopic imaging of tumor metabolism in combination with baseline functional properties of oxygenation, as measured through tumor oxygen saturation levels, shows promise for clinical outcome prediction in breast cancer NAT. 37 Specifically, in the most recent published study, 34 patients were evaluated and the responders (about 30% attained pCR) demonstrated a greater decrease in the tissue optical index than non-pCR at the half way point of therapy. Other parameters investigated in single-center studies evaluating response to NAT in breast cancers were concentrations of deoxy-hemoglobin, oxy-hemoglobin, water, and lipids, which have shown sensitivity to microvasculature, cellular metabolism, angiogenesis, edema, hypoxia, and necrosis.…”
Section: Emerging Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…36 A recent multi-center trial showed that diffuse optical spectroscopic imaging of tumor metabolism in combination with baseline functional properties of oxygenation, as measured through tumor oxygen saturation levels, shows promise for clinical outcome prediction in breast cancer NAT. 37 Specifically, in the most recent published study, 34 patients were evaluated and the responders (about 30% attained pCR) demonstrated a greater decrease in the tissue optical index than non-pCR at the half way point of therapy. Other parameters investigated in single-center studies evaluating response to NAT in breast cancers were concentrations of deoxy-hemoglobin, oxy-hemoglobin, water, and lipids, which have shown sensitivity to microvasculature, cellular metabolism, angiogenesis, edema, hypoxia, and necrosis.…”
Section: Emerging Strategiesmentioning
confidence: 99%
“…36,8183 Combining the tumor oxygen saturation with the function properties of tissue optical index, demonstrated an area under the ROC of 0.83. 37 …”
Section: Emerging Strategiesmentioning
confidence: 99%
“…These reconstructed quantities have been shown to discriminate between malignant and healthy tissue in the breast (Srinivasan et al 2005, Spinelli et al 2005, Cerussi et al 2006, Choe et al 2009, Wang et al 2010, Fang et al 2011, Mastanduno et al 2014). Importantly, several studies have employed DOSI techniques to investigate functional changes in malignant tissue over the course of NAC and have correlated these changes with the patients’ responses to treatment (Choe et al 2005, Tromberg et al 2005, Zhou et al 2007, Cerussi et al 2007, Zhu et al 2008, Jiang et al 2009, Soliman et al 2010, Cerussi et al 2011, Roblyer et al 2011, Falou et al 2012, Ueda et al 2012, Choe and Durduran 2012, Busch et al 2013a, Tromberg et al 2016, Sajjadi et al 2017). The present paper is focused on another diffuse optical technique, diffuse correlation spectroscopy (DCS), which utilizes the temporal fluctuations of detected light intensity to probe microvasculature blood flow in deep tissue (Durduran et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies aiming to predict therapeutic response early in the treatment have shown significant differences between responders and non-responders one day [14] or one week [12, 27, 32, 33] after the start of therapy. Other studies report the response during the course of treatment, typically using 3–8 measurement time points, to determine if and when different therapeutic response levels can be distinguished during NAC [13, 15, 16, 20, 21, 26, 28, 3437]. The primary focus of these studies has been on the chromophore concentrations measured at the tumor location over time, but some work has also focused on exploring the correlation between baseline, pre-treatment optical measurements and the level of response to NAC [16, 21, 38, 39].…”
Section: Introductionmentioning
confidence: 99%
“…When monitoring patients throughout the duration of therapy, hemoglobin parameters seemed to best differentiate response groups. In particular, as can be seen in Table 1, a consistent response to NAC is a decrease in the concentration of hemoglobin (often separated into the two components of oxy- and deoxy-hemoglobin) at the tumor location [12, 13, 1517, 20, 21, 26, 28, 3034, 36, 37, 41]. …”
Section: Introductionmentioning
confidence: 99%